2018
DOI: 10.1016/j.scitotenv.2018.05.030
|View full text |Cite
|
Sign up to set email alerts
|

Unconventional oil and gas chemicals and wastewater-impacted water samples promote adipogenesis via PPARγ-dependent and independent mechanisms in 3T3-L1 cells

Abstract: Unconventional oil and natural gas (UOG) operations have contributed to a surge in domestic oil and natural gas production in the United States, combining horizontal drilling with hydraulic fracturing to unlock previously inaccessible fossil fuel deposits. >1000 organic chemicals are used in the production process, and wastewater is produced following injection and for the life of the producing well. This wastewater is typically disposed of via injecting into disposal wells for long-term storage, treatment and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 75 publications
(133 reference statements)
0
14
0
Order By: Relevance
“…Increased risks of obesity in human adults exposed prenatally to DES have also been reported (34), delineating apparent translational effects. Our lab has recently demonstrated that common chemicals and environmental mixtures associated with unconventional oil and gas (UOG) operations can activate the peroxisome proliferator activated receptor gamma (PPARγ) and promote triglyceride accumulation and pre-adipocyte proliferation in vitro (35), and that gestational exposure to a mixture of UOG chemicals resulted in increased body weights through weaning in a rodent model (36, 37). UOG development has also been associated with increased prevalence of low birth weight and small for gestational age births in the Northeast US (38), and decreased prevalence of low birth weights and increased risk of higher birth weight babies in Colorado (39); both low (40, 41) and high (42, 43) birth weights are associated with greater risks for obesity later in life.…”
Section: Endocrine Disruptors As Causative Factor In Metabolic Disrupmentioning
confidence: 99%
See 2 more Smart Citations
“…Increased risks of obesity in human adults exposed prenatally to DES have also been reported (34), delineating apparent translational effects. Our lab has recently demonstrated that common chemicals and environmental mixtures associated with unconventional oil and gas (UOG) operations can activate the peroxisome proliferator activated receptor gamma (PPARγ) and promote triglyceride accumulation and pre-adipocyte proliferation in vitro (35), and that gestational exposure to a mixture of UOG chemicals resulted in increased body weights through weaning in a rodent model (36, 37). UOG development has also been associated with increased prevalence of low birth weight and small for gestational age births in the Northeast US (38), and decreased prevalence of low birth weights and increased risk of higher birth weight babies in Colorado (39); both low (40, 41) and high (42, 43) birth weights are associated with greater risks for obesity later in life.…”
Section: Endocrine Disruptors As Causative Factor In Metabolic Disrupmentioning
confidence: 99%
“…We further documented AR and TR antagonist activities in surface, ground, and/or drinking water near UOG operations in several regions, including CO, WY, WV, and ND [(268), Kassotis et al, in preparation, (269271)], and evaluated a mixture of 23 common UOG chemicals via a gestational exposure experiment in C57 mice, reported putative metabolic effects (offspring exhibited increased body weights, among other effects) (36, 37). We further interrogated this by evaluating the ability of this 23-mix, several UOG wastewater samples, and several UOG wastewater-impacted surface water samples to stimulate adipogenesis in 3T3-L1 cells and activate PPARγ in a reporter gene assay (35). We demonstrated that UOG wastewater samples exhibited significant triglyceride accumulation and/or pre-adipocyte proliferation at relative water concentrations as low as 0.001x, UOG-impacted surface water extracts at concentrations as low as 0.04x, and the 23-mix at 1 μM; these effects co-occurred with PPARγ activation for some samples but not others (35), suggesting differing mechanisms.…”
Section: Metabolic Disruption Potential Of Environmental Mixturesmentioning
confidence: 99%
See 1 more Smart Citation
“…[4,5] Therefore, numerous technologies have been developed to deal with this water pollution, such as magnetic separation, chemical dispersant, absorption and biological treatment. [6][7][8] Among those approaches, the oil absorption is believed to be the most efficient method with simple operations, low cost and environmentally friendly. [9] However, traditional sorbents remain with several drawbacks due to the low absorption efficiency and capacity, limiting the practical application.…”
Section: Introductionmentioning
confidence: 99%
“…[9] However, traditional sorbents remain with several drawbacks due to the low absorption efficiency and capacity, limiting the practical application. [10] To overcome those issues, many porous sorbents were examined to deal with oil spill and chemical leakage, such as electrospun membrane, [6] nonwoven fabric, [7] aerogel [8] and composite. [11] Those sorbents show excellent hydrophobicity, high specific surface area (SSA) and high oil absorption capacity.…”
Section: Introductionmentioning
confidence: 99%